Preparation method of organic Schiff base polymer lithium ion battery negative electrode material containing thiophene structure

By using a combination of organic Schiff base polymer containing thiophene structure and sodium alginate binder in lithium-ion batteries, the capacity and cost problems of inorganic electrode materials are solved, and the conductivity and rate performance of organic electrode materials are improved. , achieving high energy density and long life battery performance.

CN119297212AActive Publication Date: 2025-01-10ANHUI UNIV

Patent Information

Application Number
CN202411397870.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The inorganic electrode materials of existing lithium-ion batteries have problems such as capacity limitation, high prices, scarce resources, low conductivity of organic electrode materials, easy dissolution of active substances and poor rate performance, which affects the high energy density and long life requirements of the battery.

Method used

The organic Schiff alkali polymer containing thiophene structure is used as the negative electrode material, and the conjugated structure is formed by using the thiophene ring and carbon-nitrogen double bond, combined with sodium alginate as the binder, mixed uniformly through a mortar and then applied to the copper foil for vacuum. The electrode sheets are dried to form negative electrode materials with high conductivity and high magnification performance.

Benefits of technology

It significantly improves the cycle stability and high rate performance of the battery, has high reversible specific capacity, is simple in synthesis and low in cost, and is suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297212A_ABST
    Figure CN119297212A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an organic Schiff base polymer lithium ion battery negative electrode material containing a thiophene structure, and belongs to the technical field of lithium ion battery organic electrode materials. A thiophene ring and a carbon-nitrogen double bond are used as a framework of the polymer, so that the polymer has an extended conjugated structure, strong electron delocalization, a stable structure and high conductivity. Compared with the existing organic negative electrode material, the thienyl Schiff base polymer lithium ion battery negative electrode material (PDTS) prepared by the preparation method disclosed by the invention has relatively high reversible specific capacity and very excellent rate capability under high current density. The negative electrode material not only greatly improves the cycling stability of the battery, but also has high rate capability and high reversible specific capacity, is very simple to synthesize, high in yield and low in cost, and has a very good large-scale application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic lithium ion battery electrode materials, and in particular relates to a method for preparing an organic Schiff base polymer lithium ion battery negative electrode material containing a thiophene structure. Background Art

[0002] With the development of human society, the global demand for renewable energy and energy conservation and environmental protection continues to increase. In order to meet this challenge, rechargeable lithium-ion battery technology has been widely studied. At present, the use of mobile devices such as laptops and mobile phones is increasing. At the same time, new energy vehicles are developing rapidly, the scale of energy storage equipment is increasing, and the requirements for lithium-ion batteries are getting higher and higher. Therefore, there is an urgent need for new high-performance lithium-ion batteries with high energy density and long life.

[0003] Most of the lithium-ion batteries currently used in the market are made of inorganic materials, and traditional battery materials have many limitations. For example, traditional inorganic lithium-ion battery electrode materials have problems such as capacity limitations, high prices, and scarce resources. These limitations have prompted people to begin to pay attention to and study organic electrode materials. Organic electrode materials have the advantages of high molecular design freedom, the ability to achieve a variety of electrochemical reactions, low cost, and environmental friendliness, which can bring broader development space for battery design.

[0004] There are also many problems with organic electrode materials, such as low conductivity and active substances being easily soluble in electrolytes. In order to solve the above problems, a good solution is to use a polymer skeleton to connect active groups to form a highly conjugated system. In addition, organic electrode materials generally have the problem of poor rate performance, and the selection of a suitable binder is also a major factor affecting electrode performance. A suitable binder can make the electrode have low impedance and better stability. Therefore, it is necessary to reasonably design the polymer skeleton and select a suitable binder to give it a high specific capacity and strong cycle performance. Summary of the invention

[0005] In view of the deficiencies of the above-mentioned prior art, the present invention provides a method for preparing an organic Schiff base polymer lithium ion battery negative electrode material containing a thiophene structure. The negative electrode material of the present invention uses a thiophene ring and a carbon-nitrogen double bond as the skeleton of the polymer, so that it has an extended conjugated structure, strong electron delocalization, a stable structure and a large conductivity; sodium alginate is used as a binder, and it has very excellent rate performance at high current density, which not only greatly improves the cycle stability of the battery, but also has high rate performance and high reversible specific capacity, and the synthesis is very simple, the yield is high, the cost is low, and it has very good prospects for large-scale application.

[0006] The method for preparing the organic Schiff base polymer lithium ion battery negative electrode material containing thiophene structure of the present invention comprises the following steps:

[0007] The organic Schiff base polymer material containing a thiophene structure, Ketjen black and a binder sodium alginate are mixed evenly in a mortar, and then deionized water is added as a solvent, and grinding is continued for 10-15 minutes to obtain a uniform viscous slurry; the obtained slurry is evenly coated on a copper foil, and vacuum dried to obtain a thiophene-based Schiff base polymer lithium-ion battery negative electrode sheet.

[0008] The raw materials are composed of 50-80 parts of organic Schiff base polymer material containing thiophene structure, 10-40 parts of Ketjen black, and 10 parts of sodium alginate as a binder in terms of mass fraction. The total amount is controlled to be 100 parts.

[0009] The electrode drying temperature is 60-80℃ and the drying time is 12-18h.

[0010] The general structural formula of the organic Schiff base polymer containing a thiophene structure is shown below:

[0011]

[0012] Where n represents the degree of polymerization, ranging from 10-500.

[0013] The organic Schiff base polymer containing a thiophene structure is prepared by the following method:

[0014] Under a nitrogen atmosphere, 0.2-0.6 g of p-phenylenediamine and 0.3-0.7 g of 2,5-thiophene dicarboxaldehyde are uniformly dispersed in 30-50 mL of anhydrous ethanol, 2-3 drops of catalyst are added, and then heated to reflux for 8-12 h under magnetic stirring, the reaction temperature is 65-78 ° C, and the reaction is cooled to room temperature after completion; the reaction liquid is filtered to collect the orange-red solid; the collected orange-red solid is placed in a Soxhlet extractor, extracted with toluene and ethanol for 12-18 h, respectively, and vacuum dried for 8-12 h to obtain an organic Schiff base polymer containing a thiophene structure.

[0015] Furthermore, the molar ratio of p-phenylenediamine to 2,5-thiophenedicarboxaldehyde is 1:1.

[0016] Furthermore, the vacuum drying temperature is 60-80°C.

[0017] The catalyst is selected from one of an acidic catalyst and a basic catalyst. The acidic catalyst is selected from acetic acid, hydrochloric acid, formic acid or p-toluenesulfonic acid; the basic catalyst is selected from ammonia water, sodium hydroxide or potassium hydroxide.

[0018] The purity of the p-phenylenediamine is higher than 99%, the purity of 2,5-thiophenedicarbaldehyde is higher than 98%, and the viscosity of the sodium alginate is 500-1000 mPa·s.

[0019] The reaction route is as follows:

[0020]

[0021] The negative electrode sheet of the lithium-ion battery prepared by the present invention is cut into a circular sheet with a diameter of 10 to 12 mm, and a lithium sheet with a diameter of 16 mm is used as a counter electrode. The diaphragm uses a Celgard 2325 microporous three-layer membrane, and the electrolyte is lithium hexafluorophosphate (LiPF6) dissolved in dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) solvents, with a volume ratio of DMC:DEC:EMC=1:1:1, and the concentration of lithium hexafluorophosphate is 1 mol / L. CR2032 button batteries are assembled in a glove box filled with argon; the oxygen concentration is not higher than 1 ppm, and the water vapor concentration is not higher than 0.5 ppm.

[0022] Compared with other organic negative electrode materials, the organic Schiff base polymer lithium ion battery negative electrode material containing thiophene structure prepared by the present invention has the advantage of having very excellent rate performance at high current density, which not only greatly improves the cycle stability of the battery, but also has high rate performance and high reversible specific capacity, and the synthesis is very simple, so it is a very competitive organic negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the CV curve of the PDTS electrode.

[0024] Figure 2 This is the cycle of PDTS electrode at a current density of 0.2 A / g.

[0025] Figure 3 This is the cycle of PDTS electrode at a current density of 1 A / g.

[0026] Figure 4 is the cycle rate of the PDTS electrode.

[0027] Figure 5 Coating the PDTS electrode sheet. DETAILED DESCRIPTION

[0028] The present invention will be further described in detail below in conjunction with specific embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0029] Embodiment 1:

[0030] Under nitrogen atmosphere, p-phenylenediamine (0.216g, 2mmol) and 2,5-thiophene dicarboxaldehyde (0.280g, 2mmol) were uniformly dispersed in 40mL of anhydrous ethanol solution, 2-3 drops of glacial acetic acid were added as a catalyst, and then heated under reflux for 8-12h under magnetic stirring, the reaction temperature was 60-78℃, and after the reaction was completed, it was cooled to room temperature, and the obtained mixed solution was filtered to obtain an orange-red solid, and then the obtained orange-red solid was placed in a Soxhlet extractor, extracted with toluene and ethanol for 12-18h, respectively, and vacuum dried at 60-80℃ for 8-12h to obtain a lithium ion battery negative electrode material (PDTS) containing a thiophene ring. The yield was 83%.

[0031] PDTS was used as an active material and mixed with Ketjen black and sodium alginate (SA) in a mortar at a mass ratio of 5:4:1. Deionized water was added as a solvent and the mixture was ground and stirred for 10 minutes to form a uniform viscous slurry. The slurry was coated on a copper foil with a scraper and dried in vacuum at 60°C for 12 hours to obtain a thiophene-based poly Schiff base lithium-ion battery negative electrode sheet (such as Figure 5 PDTS@SA), and then cut it into a circular electrode with a diameter of 12mm, with a lithium sheet with a diameter of 16mm as the counter electrode, Celgard2325 as the separator, and a mixed solution with a volume ratio of DMC:DEC:EMC=1:1:1 as the electrolyte, and assembled into a CR2032 button cell in an argon-filled glove box. The battery was subjected to cyclic voltammetry test. The large reduction peak in the first cycle corresponds to the formation of the SEI film, and the CV curves of the second and third cycles are almost overlapped (as shown in Figure 2). Figure 1 The constant current charge and discharge test of the battery with this formula shows that the first charge and discharge capacities reach 3009.7mAh / g and 1312.1mAh / g respectively at a current density of 0.2A / g (as shown in Figure 2), indicating that the product of the present invention has good cycle stability. Figure 2 PDTS@SA541), after 10 cycles, the specific capacity is stable at about 1000mAh / g, which is much larger than the graphite anode on the market (360mAh / g); at a high current density of 1A / g, the specific capacity is maintained at about 469.5mAh / g (as shown in Figure 3 PDTS@SA541), the rate performance test shows that the specific capacity decreases continuously when the current density increases, and the specific capacity recovers when the current density is restored to a small value, indicating that it has a good rate performance (such as Figure 4 PDTS@SA541).

[0032] Embodiment 2:

[0033] The PDTS prepared in Example 1 was used as an active material and mixed evenly with Ketjen black and sodium alginate (SA) in a mortar at a mass ratio of 6:3:1, deionized water was added as a solvent, and grinding and stirring were continued for 10 minutes to mix into a uniform viscous slurry; the slurry was coated on a copper foil with a scraper, and vacuum dried at 60°C for 12 hours to obtain a thienyl poly Schiff base lithium ion battery negative electrode plate, which was then cut into a circular plate with a diameter of 12 mm, a lithium sheet with a diameter of 16 mm was used as a counter electrode, Celgard2325 was used as a diaphragm, and a mixed solution with a volume ratio of DMC:DEC:EMC=1:1:1 was used as an electrolyte, and a CR2032 button battery was assembled in a glove box filled with argon. The formula battery was subjected to constant current charge and discharge tests. At a current density of 0.2A / g, the initial charge and discharge capacities reached 1748.5mAh / g and 746.9mAh / g respectively. After 10 cycles, the specific capacity stabilized at 655mAh / g, and at a high current density of 1A / g, the specific capacity was maintained above 250mAh / g. The rate performance test was also carried out. The specific capacity continued to decrease when the current density increased, and recovered when the low current density was restored, indicating that it still has good rate performance.

[0034] Embodiment 3:

[0035] The PDTS prepared in Example 1 was used as an active material and mixed evenly with Ketjen black and sodium alginate (SA) in a mortar at a mass ratio of 7:2:1, deionized water was added as a solvent, and grinding and stirring were continued for 10 minutes to mix into a uniform viscous slurry; the slurry was coated on a copper foil with a scraper, and vacuum dried at 60°C for 12 hours to obtain a thienyl poly Schiff base lithium ion battery negative electrode sheet, which was then cut into a circular sheet with a diameter of 12 mm, a lithium sheet with a diameter of 16 mm was used as a counter electrode, Celgard2325 was used as a diaphragm, and a mixed solution with a volume ratio of DMC:DEC:EMC=1:1:1 was used as an electrolyte, and a CR2032 button battery was assembled in a glove box filled with argon. The formula battery was subjected to constant current charge and discharge tests. At a current density of 0.2A / g, the initial charge and discharge capacities reached 1762.4mAh / g and 904.4mAh / g respectively. As the cycle progressed, the capacity slowly decreased, which may be due to poor conductivity. This is also illustrated by the fact that the specific capacity was only maintained at around 200mAh / g at a high current density of 1A / g. The rate performance test was also carried out. The specific capacity continued to decrease when the current density increased, and recovered when the low current density was restored, but the overall specific capacity was low.

[0036] Comparative Example 1:

[0037] The PDTS prepared in Example 1 was used as an active material and mixed evenly with Ketjen black and polyvinylidene fluoride (PVDF) in a mortar at a mass ratio of 5:4:1. NMP solution was added as a solvent, and grinding and stirring were continued for 10 minutes to mix into a uniform viscous slurry. The slurry was coated on a copper foil with a scraper and vacuum dried at 80°C for 12 hours to obtain a thienyl poly Schiff base lithium ion battery negative electrode sheet. However, since PDTS is soluble in NMP and has a small intermolecular force with PVDF, its film-forming property is poor (such as Figure 5 PDTS@PVDF541), the electrode was cut into a circular electrode with a diameter of 12mm, a lithium sheet with a diameter of 16mm was used as the counter electrode, Celgard 2325 was used as the separator, and a mixed solution with a volume ratio of DMC:DEC:EMC=1:1:1 was used as the electrolyte. The CR2032 button battery was assembled in a glove box filled with argon. The formula battery was subjected to constant current charge and discharge tests. At a current density of 0.2A / g, the initial charge and discharge capacities reached 1914.9mAh / g and 757.2mAh / g, respectively. After 20 cycles, the specific capacity was stabilized at 352mAh / g (as shown in Figure 2). Figure 2 PDTS@PVDF541); at a high current density of 1A / g, the specific capacity is maintained at around 200mAh / g (as shown in Figure 3 PDTS@PVDF541); the rate performance test was also carried out, and the specific capacity continued to decrease when the current density increased, and the specific capacity recovered when the low current density was restored (as shown in Figure 4 PDTS@PVDF541), indicating that it has good rate performance. However, its overall performance is inferior to that of SA binder.

[0038] Comparative Example 2:

[0039] The PDTS prepared in Example 1 was used as an active material and was mixed evenly with Ketjen black and carboxymethyl cellulose (CMC) in a mortar at a mass ratio of 5:4:1. An aqueous solution was added as a solvent, and grinding and stirring were continued for 10 minutes to mix into a uniform viscous slurry; the slurry was coated on a copper foil with a scraper, and vacuum dried at 60°C for 12 hours to obtain a thienyl poly Schiff base lithium ion battery negative electrode plate, which was then cut into a circular plate with a diameter of 12 mm, a lithium sheet with a diameter of 16 mm was used as a counter electrode, Celgard2325 was used as a diaphragm, and a mixed solution with a volume ratio of DMC:DEC:EMC=1:1:1 was used as an electrolyte, and a CR2032 button battery was assembled in a glove box filled with argon. The formula battery was subjected to constant current charge and discharge tests. At a current density of 0.2A / g, the initial charge and discharge capacities reached 3217.7mAh / g and 1586.5mAh / g respectively. After 20 cycles, the specific capacity stabilized at around 700mAh / g. At a high current density of 1A / g, the specific capacity was maintained at 200mAh / g. The rate performance test was also carried out. The specific capacity continued to decrease when the current density increased, and recovered when the low current density was restored, indicating that it has good rate performance, but the overall performance is still weaker than that of sodium alginate binder.

Claims

1. A method for preparing an organic Schiff base polymer lithium ion battery negative electrode material containing a thiophene structure, characterized in that: The organic Schiff base polymer material containing a thiophene structure, Ketjen black and a binder sodium alginate are mixed evenly in a mortar, and then deionized water is added as a solvent, and grinding is continued to obtain a uniform viscous slurry; the obtained slurry is evenly coated on a copper foil, and vacuum dried to obtain a thiophene Schiff base polymer lithium ion battery negative electrode sheet; The general structural formula of the organic Schiff base polymer containing a thiophene structure is shown below: Where n represents the degree of polymerization, ranging from 10-500.

2. The preparation method according to claim 1, characterized in that: The raw materials are composed of 50-80 parts of organic Schiff base polymer material containing thiophene structure, 10-40 parts of Ketjen black, and 10 parts of sodium alginate as a binder, and the total amount is controlled to be 100 parts.

3. The preparation method according to claim 1, characterized in that: The organic Schiff base polymer containing a thiophene structure is prepared by the following method: Under a nitrogen atmosphere, p-phenylenediamine and 2,5-thiophenedicarboxaldehyde are uniformly dispersed in anhydrous ethanol, a catalyst is added dropwise, and then heated to reflux reaction for 8-12 hours under magnetic stirring. After the reaction is completed, it is cooled to room temperature; the reaction liquid is filtered to collect the orange-red solid; the collected orange-red solid is placed in a Soxhlet extractor, extracted with toluene and ethanol for 12 to 18 hours, respectively, and vacuum dried to obtain an organic Schiff base polymer containing a thiophene structure.

4. The preparation method according to claim 3, characterized in that: The molar ratio of p-phenylenediamine to 2,5-thiophenedicarbaldehyde is 1:

1.

5. The preparation method according to claim 1, characterized in that: The viscosity of the sodium alginate is 500-1000 mPa·s.

6. The preparation method according to claim 3, characterized in that: The catalyst is selected from one of an acidic catalyst and a basic catalyst.

7. The preparation method according to claim 6, characterized in that: The acidic catalyst is selected from acetic acid, hydrochloric acid, formic acid or p-toluenesulfonic acid.

8. The preparation method according to claim 6, characterized in that: The alkaline catalyst is selected from ammonia water, sodium hydroxide or potassium hydroxide.

Citation Information

Patent Citations

  • Preparation method and application of COFs material constructed based on semi-carbonization method

    CN116429846A

  • Polyamic acid and polyimide

    JP2002338686A

  • Battery having electrode made of polymeric compound having conjugated double bonds

    US4544615A

  • Non-aqueous electrolytes and uses thereof

    WO2017167638A1

Cited By

  • High-capacity silicon-based negative electrode material and preparation method and application thereof

    CN120089745A

  • A high-capacity performance silicon-based anode material, its preparation method and application

    CN120089745B

  • Ternary positive electrode material of Schiff base-manganese compound and preparation method of ternary positive electrode material

    CN121484001A